Frequency of Hypernatremia Among Children Below 2 Years Presenting with Acute Gastroenteritis - Hameed, Rimsha; Babar, Habibullah; Bizenjo, Attaullah; Rayaz, Saima; Iqbal, Mohammad; Abdullah, Hafiz (Indus Journal of Bioscience Research, 2025)
Background: Acute gastroenteritis functions as a primary reason for hospital admissions and death among children less than two years old within developing nations. The complications that frequently affect patients include dehydration together with electrolyte disturbances. Clinical risks from hypernatremia remain serious because this condition affects young infants more than hyponatremia does through severe neurological consequences. Objectives: A study was conducted to measure hypernatremia rates among children younger than two who visit medical facilities due to acute gastroenteritis. This evaluation determined demographic and presentation-related factors linked to hypernatremia status. Study design: A cross-sectional study. Place and duration of study: From 19 Oct 2023 to 18 April 2024 Paediatrics Department, Bolan Medical College/ Hospital Quetta. Balochistan. Methods: A six-month data collection took place at the Department of Paediatrics within Bolan Medical College/ Hospital Quetta. Sixty-six children beneath the age of two-faced acute gastroenteritis during the study and received enrollment through consecutive sampling. The medical staff obtained sodium measurements from blood plasma when patients joined the study. The study utilized two criteria for identifying patients with hypernatremia: serum sodium greater than 145 mmol/L. Data evaluation took place with SPSS version 24.0. The studyers computed mean results alongside standard deviation and p-values as they established p<0.05 as their significance threshold. Results: Among 166 enrolled children, 38 (22.9%) had hypernatremia. The study participants averaged 11.2 ± 5.4 months in age. The children who had hypernatremia mostly came from two groups: prolonged diarrhea cases of more than three days and improper feeding practices as well as no use of oral rehydration. The study data indicated a positive statistical link between hypernatremia and prolonged diarrhea duration (p = 0.016) together with inadequate fluid choices at home (p = 0.032). The study results failed to identify any meaningful relationship between gender and hypernatremic conditions (p = 0.412). The study results demonstrate that improper home care and slow hospital attendance contribute to the development of hypernatremia in children. Conclusion: Acute gastroenteritis in children under two years causes substantial hypernatremia while remaining unrecognized as an electrolyte imbalance in most cases. Patients who have hypernatremia show a direct connection to both extended sickness and erroneous fluid treatment before hospital admission. Regular serum sodium tests along with proper water replacement education for caregivers protect children from major complications. The timely identification and treatment of this condition leads to better medical results and decreases suffering from complications.